User Experience Lifecycle pada Aplikasi Knowledge Management System Inovasi Desa - Ariq Cahya Wardhana; Condro Kartiko; Wahyu Andi Saputra; Tio Fani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Indonesia is a country based on the village. The number of villages in Indonesia increases every year due to regional expansion in several regions. The division serves to reduce disadvantaged areas. Development management is needed to reduce underdeveloped areas. One of them is village development activities that must be able to give birth to creative and innovative habits. The Village Innovation Knowledge Management System is a medium to initiate the transformation of knowledge and practice between villages. The system needs to be assessed and evaluate its performance to see how far the level of success is on the user side. Based on these problems, it is necessary to develop the User Experience Lifecycle (UXL) method. UXL has four stages, namely analysis, design, prototype, and evaluation. Interviews were conducted with 7 participants to find the main problems. The problems obtained are then analyzed and converted into a system that can be used by users. The system that has been created is then started with the use of testing using think-aloud and System Usability Scale. The results of think-aloud show a positive impression of the participants. While the System Usability Scale gets a score of 74.5 which is categorized as good (B).